2011
DOI: 10.1029/2010ja016032
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthal auroral expansion associated with fast flows in the near-Earth plasma sheet: Coordinated observations of the THEMIS all-sky imagers and multiple spacecraft

Abstract: [1] Fast azimuthal auroral expansion and poleward expansion are characteristic features of the expansion phase of substorms. In the first study of its kind, we have investigated the azimuthal auroral expansion and its magnetospheric counterpart using data from Time History of Events and Macroscale Interactions during Substorms (THEMIS) all-sky imagers and multiple spacecraft. During the tail season in 2008-2009, we found 16 events of azimuthally expanding aurora that passed near the magnetic footprints of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…The speed match along the azimuthal direction among the dipolarization, density structure, and plasma motion suggests that the dipolarization propagated along with plasma motion. This speed will be further discussed and compared to previous studies (Angelopoulos et al., 2008; Nagai, 1982; Ogasawara et al., 2011; Ohtani et al., 2018) in Section 4. RBSP‐A and ‐B were in the PSBL before around 05:05 UT, when both spacecraft saw increases in the electron temperature from several keV to several 10s of keV and electron density from several 0.1s to above 1 cm −3 (not shown).…”
Section: Observationsmentioning
confidence: 77%
See 1 more Smart Citation
“…The speed match along the azimuthal direction among the dipolarization, density structure, and plasma motion suggests that the dipolarization propagated along with plasma motion. This speed will be further discussed and compared to previous studies (Angelopoulos et al., 2008; Nagai, 1982; Ogasawara et al., 2011; Ohtani et al., 2018) in Section 4. RBSP‐A and ‐B were in the PSBL before around 05:05 UT, when both spacecraft saw increases in the electron temperature from several keV to several 10s of keV and electron density from several 0.1s to above 1 cm −3 (not shown).…”
Section: Observationsmentioning
confidence: 77%
“…This speed corresponds to dipolarizations propagate at 150 km/s at geosynchronous orbit along the azimuthal direction. Although such “fast” dipolarizations are reported in many events (Angelopoulos et al., 2008; Ogasawara et al., 2011), statistical studies show that the typical value of the azimuthal phase speed of the dipolarizations is only 30–50 km/s (Nagai, 1982; Ohtani et al., 2018) at geosynchronous orbit. In Section 4, we discuss the nature of the “fast” dipolarizations, the apparent speed difference between the “fast” and “slow” dipolarizations, and their relation to the auroral motion and Alfvenic Poynting flux.…”
Section: Introductionmentioning
confidence: 99%
“…The sustained dipolarization's azimuthal propagation speed fully agrees with the statistical results of Liou et al (), who found that dipolarization propagation velocities are ~60 km/s eastward and ~75 km/s westward at geosynchronous orbit. Ogasawara et al () found consistency between auroral azimuthal expansion and dipolarization propagation. Their velocities were larger (267 km/s); however, they focused on bulge expansion in the vicinity of substorm onset where changes occur rapidly.…”
Section: Discussionmentioning
confidence: 93%
“…In particular, we find that within ~60 s prior to the substorm onset the auroral wave-like arc structure moves westward with average moving velocity about the same as the phase velocity of the westward propagating Pi2 δ B y disturbance observed by the THEMIS D and THEMIS E (Th D and Th E) satellites if the Pi2 disturbance activity is mapped by using the T96 model (Tsyganenko 1995 ) to the ionosphere. This substorm event was previously examined by Pu et al ( 2010 ) in relation with magnetic reconnection in the magnetotail and by Ogasawara et al ( 2011 ) on the relation between the auroral features and magnetispheric plasma flow and B z dipolarization which occurred just after the auroral expansion onset. Here, we focus on the dynamics of the wave-like substorm arc prior to the substorm onset and its relationship with the corresponding Pi2 disturbance activity in the near-Earth plasma sheet.…”
Section: Methodsmentioning
confidence: 88%
“…But, the Th E spacecraft observes the magnetic B z dipolarization at ~0405:00 UT probably because it is located further away from the substorm initiation region in the plasma sheet. In both Th D and Th E spacecraft observations, the magnetic B z dipolarization is accompanied by a significant increase in plasma flow, wave fluctuations, and high energy ion flux (Pu et al 2010 ; Ogasawara et al 2011 ).
Fig.
…”
Section: Methodsmentioning
confidence: 99%